Development of STEM Learning Activities on the Water Cycle to Enhance the Achievement of Grade 5 Students - Sukkamo, Titiporn; Prasertsang, Parichart (International Journal of STEM Education for Sustainability, 2024)
This research aimed to 1) Develop STEM learning activities for Grade 5 students on the water cycle to be effective according to the 70/70 criteria. 2) Compare achievement before and after studying. After using STEM education activities About the water cycle. 3) Study student satisfaction with science learning activities. The sample for this research was 21 students in Grade 5 at a School at Chaturaphak Phiman District, Roi Et Province, Thailand obtained from random sampling, using the school as the random unit. The tools used include 1) 3 Lesson plans 2) an Achievement test for science subjects, Grade 5, Unit 4 The Water Cycle was a multiple choice test with 4 options, 30 questions. 3) an Assessment of student satisfaction with learning activities using STEM education using the evaluation scale has 5 levels and 12 items. Statistics used in data analysis include percentages, averages, and standard deviations and statistics test the value of t. The results of the research found that STEM learning activities on the water cycle to enhance the achievement of Grade 5 students were highly effective at criteria of 86/76.5. The academic achievement of Grade 5 students after studying was higher than before studying at a statistical significance at the .05 level and student satisfaction with organizing STEM learning activities on The Water Cycle to enhance the achievement of Grade 5 was at the highest level.